Estratégias biológicas para tratabilidade de água em processo de fabricação de papel reciclado - Dick, Júlia Gabriela (My University, 2023)
The pulp and paper industries are responsible for about 1% of the entire Brazilian GDP, and are considered economic indicators for reflecting the variations in the commercial market. Among these industrial plants, we can distinguish the recycled paper mills, which operate in the production of paper from trimmings derived from the recycling of cardboard previously sold. As a result of the physical- chemical characteristics of the chips and the use of other inputs, by-products are generated that alter the color, turbidity, electrical conductivity and other parameters, which influence the performance of the production process. These aspects can be accentuated when considered plants with no effluent disposal. In closed systems, as a consequence of water reuse in the production process, an increase in the percentage of contaminants is identified, which also interferes in final product characteristics. Fungal cultures have been used in order to minimize these effects in a sustainable way in pulp and paper, textile, and galvanic industries, among others. In the present work, cultivations of Pleurotus albidus and Lentinus crinitus were carried out aiming to improve the water quality of a recycled paper industry in a closed system. The cultivations were performed in media composed by different percentages of recycling water (30 to 90% v/v) and glucose (0 to 20 g/L), at 28oC, in flasks under agitation. Among the conditions evaluated for P. albidus, mean values of reduction of color and electrical conductivity of the medium of 88 and 30% were attained, respectively, in medium formulated with 90% (v/v) of recycling water and glucose, in 9 days of process. In L. crinitus cultivation less cell growth was quantified, but the constitutive production of lacases using 90% (v/v) of recycling water was about 10 times higher than that obtained with P. albidus. Considering the reduction of color and electrical conductivity, the results were similar to those achieved in P. albidus cultures. With 90% (v/v) of recycle water and glucose supplementation, an average reduction of 30% of electrical conductivity was obtained by L. crinitus on the 3rd day of cultivation and 70% of color in 9 days of process. The results presented clean and sustainable alternatives for improving water quality in paper industries with the closure of the water and effluent circuit and with recycled raw materials. [resumo fornecido pelo autor]
As indústrias de celulose e papel são responsáveis por cerca de 1% de todo o PIB brasileiro, sendo consideradas sinalizadores econômicos por refletirem as variações do mercado comercial. Dentre estas plantas industriais, distinguem-se as fábricas de papel reciclado, que atuam na produção de papel a partir de aparas provenientes da reciclagem do papelão previamente comercializado. Em decorrência das características físico-químicas das aparas e do uso de outros insumos, são gerados produtos de degradação que alteram a cor, turbidez, condutividade elétrica e outros parâmetros da água utilizada para fabricação de papel. Estes aspectos podem ser acentuados quando se tratam de plantas onde não há descarte de efluentes. Nos sistemas fechados, como consequência da reutilização da água no processo produtivo, é identificada a elevação do percentual de contaminantes, o que também interfere nas características do produto final. Cultivos fúngicos têm sido utilizados no intuito de minimizar estes efeitos de forma sustentável em indústrias de papel e celulose, têxtil e galvânica, entre outras. No presente trabalho, cultivos de Pleurotus albidus e Lentinus crinitus foram realizados buscando a melhora da qualidade da água de uma indústria de papel reciclado em sistema fechado. Os cultivos foram realizados em meios compostos por diferentes percentuais de água de reciclo (30 a 90% v/v) e glicose (0 a 20 g/L), a 28oC, em frascos sob agitação. Entre as condições avaliadas para P. albidus, valores médios de redução de cor e de condutividade elétrica do meio de 88 e 30% foram alcançados, respectivamente, em meio formulado com 90% de água de reciclo e glicose, em 9 dias de processo. No cultivo de L. crinitus foi quantificado menor crescimento celular, porém, a produção constitutiva de lacases com o uso de 90% de água de reciclo foi cerca de 10 vezes superior à obtida com P. albidus. Considerando a redução de cor e condutividade elétrica, os resultados foram semelhantes aos atingidos em cultivos de P. albidus. Em cultivo de L. crinitus com 90% de água de reciclo e suplementação de glicose, foi atingida redução média de 30% de condutividade elétrica no 3º dia de cultivo e 70% de cor em 9 dias de processo. Os resultados aqui apresentados direcionam para alternativas limpas e sustentáveis no que tange à melhora da qualidade da água nas indústrias de papel que trabalham com o fechamento do circuito de águas e efluentes e com matérias-primas recicladas. [resumo fornecido pelo autor]
Keywords: Industria de celulose; Papel - Confecção; Água - Purificação - Tratamento biológico; Enzimas - Aplicações industriais; Cellulose industry; Papermaking; Water - Purification - Biological treatment; Enzymes - Industrial applications